Information about occupations – a new resource of knowledge integrating the labour market with education - Krzysztof Symela (Edukacja Ustawiczna Dorosłych)
Information and knowledge are integrally connected with each other. They are perceived as a new good on the labour market necessary to effectively compete in contemporary information and knowledge-based society. In the case of the PO WER project “Developing, supplementing and updating information about occupations and its dissemination with the use of modern communication tools – INFODORADCA+” information concentrates on the specifics of performing of a given occupation and its working environment, describes educational requirements, employment possibilities, and professional development opportunities as well as ways to certify qualifications and professional competences defined by the learning outcomes: knowledge, skills and social competences. The joint knowledge of many thousands of experts from various areas of economic and social life and 30 months (2017–2019) of hard work done by 5 Polish institutions (project partners) resulted in the development of information about 1000 occupations. Consequently, a critical mass of the information about occupations has been achieved and it has already become a systemic tool useful for employment purposes as well as formal and non-formal education.